ANALISIS SIKAP, MOTIVASI DAN MINAT BERWIRAUSAHA (ENTREPREUNERSHIP) PADA MAHASISWA PROGRAM MAGISTER UNIVERSITAS PERTAHANAN REPUBLIK INDONESIA - Tedyansyah Tedyansyah; Maijon Kinaro (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The research focuses on how entrepreneurial values, particularly among students, are instilled, and how they are expected to foster entrepreneurial enthusiasm. The research question is how much influence behavior and motivation have on students' entrepreneurial interest. The research employed a survey method using a simple random sampling approach. Data were collected through questionnaires. The data were analyzed using SPSS software. The researchers used multiple linear regression to determine the relationship between variables. The results indicate that students' attitudes and motivation play a significant role in shaping their interest in entrepreneurship